A longitudinal observation of a patient with normal tension glaucoma - Hlupheka L. Sithole (African Vision and Eye Health, 2017)
Normal tension glaucoma (NTG) is a disease associated with normal intraocular pressure (10 mmHg – 21 mmHg) that may lead to irreversible blindness if misdiagnosed or left untreated over a period of time. The author observed a patient with NTG over a period of 5 years (from 2013 to 2017). The initial visual field analysis results (2014) showed mild visual field defects because of NTG at the start of the 5-year period. Although the patient was also diagnosed with hydrocephalus, a condition associated with optic nerve head damage, following years of noncompliance to treatment of NTG and follow-up eye examination schedules, the patient’s visual field defects were found to have progressed by the year 2017. It is therefore important for optometrists to apply due diligence when examining patients with NTG in order to expedite intervention and prevention of visual impairment and blindness.